Feasibility and efficacy of a mass switch from ranibizumab (Lucentis) to bevacizumab (Avastin) for treatment of neovascular age-related macular degeneration - Andreoli, Michael T.; Pinnolis, Michael; Kieser, Troy; Sun, Jennifer; Andreoli, Christopher M. (Digital Journal of Ophthalmology, 2015)
Objective To assess the feasibility and potential obstacles of a departmental switch from ranibizumab (Lucentis, Genentech, South San Francisco, CA) to bevacizumab (Avastin, Genentech) for the treatment of neovascular age-related macular degeneration (AMD). Methods A total of 154 eyes treated for wet AMD with ranibizumab or bevacizumab were examined over a 10-month period. The treatment protocol was monthly induction therapy followed by injections as needed for macular edema or subretinal fluid on optical coherence tomography, new hemorrhage or edema on examination, worsening vision, or leakage on fluorescein angiography. Central subfield thickness and pinhole vision were the main treatment outcomes. Study windows were compared using t tests and Mann-Whitney U tests. Statistical significance was defined as a P value of <0.05. Results The majority of patients (88%) were willing to accept a bevacizumab injection. There was no difference in frequency of injection, central subfield thickness, visual outcome, or endophthalmitis rate between the ranibizumab and bevacizumab groups. A small subset of patients (4.5%) appeared to respond more favorably to ranibizumab than bevacizumab. Conclusion Bevacizumab appears to be a cost-effective alternative to ranibizumab for the treatment of neovascular AMD. Patients previously treated with ranibizumab are typically willing to switch to bevacizumab. In the overwhelming majority of patients, there is no major decline in clinical status. However, select patients may respond better to ranibizumab injections.